Wybór opcji czy osoby? Determinanty zachowań wyborczych mieszkańców województwa podkarpackiego w wyborach do Parlamentu Europejskiego w 2014 r. w świetle badań empirycznych - Szczepański, Dominik (Political Preferences, 2015)
Selecting the person? Determinants of voting behavior inhabitants of the Subcarpathian Voivodeship in elections to the European Parliament in 2014 in the light of empirical research The aim of the article was to present factors influencing voting behaviours of the Subcarpathian Voivodeship citizens during European Parliament elections in 2014, in the light of the conducted empirical research. The indicators that guided voters when casting votes to ballot boxes were analysed on the basis of a set of variables, such as: the attractiveness of election programmes and political parties, competences of candidates, the role of the Catholic Church during the election campaign, or the awareness of voters (self-reliance in making electoral decisions or its lack). The analysis and interpretations from the conducted research were preceded by a voting description of the Subcarpathian Voivodeship, treated, on a electoral map of Poland, as a specific region due to its above average support given to candidates and parties of right-wing provenance. In the final part conclusions drawn from the analytical process were presented. Key words: personalization, Subcarpathian Voivodeship, European Parliament elections, voting behaviour